A new leaf-toed gecko (Gekkonidae: Dixonius) from the city of Ranong, southwestern Thailand - Sumontha, Montri; Pauwels, Olivier S. G. (Zootaxa, 2020)
We describe Dixonius dulayaphitakorum sp. nov. from Ranong city, Ranong Province, southern peninsular Thailand. The new, ground-dwelling species differs from all currently recognized Dixonius by a combination of morphological characters and pattern: maximal known SVL of 47.8 mm, 22 longitudinal rows of dorsal tubercles; 33 to 35 paravertebral scales; 22 longitudinal rows of ventrals across the abdomen; six or seven precloacal pores in males, no pores in females; no distinct canthal stripe; and a spotted dorsal pattern. Based on dorsal pattern, the new species seems related to Dixonius siamensis. This description brings to 11 the number of Dixonius species, and to five the ones endemic to Thailand.